2017
DOI: 10.1002/jsfa.8292
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation of oat β‐glucan and hydrolysates by fecal microbiota and selected probiotic strains

Abstract: The results of the present study indicate that oat β-glucan hydrolysates could serve as a more promising material for developing novel symbiotic foods. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
1
23
0
3
Order By: Relevance
“…Their dietary fibers, specifically soluble fibers -glucans found in the endosperm cell walls, are considered prebiotics. They serve as feed for the intestinal microflora, promoting bacterial growth during fermentation [ 31 ]. -glucans also contribute to a regulation of satiety levels [ 32 ] and act as thickening agents, increasing product viscosity [ 33 ] and avoiding the addition of other functional ingredients or stabilizers [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their dietary fibers, specifically soluble fibers -glucans found in the endosperm cell walls, are considered prebiotics. They serve as feed for the intestinal microflora, promoting bacterial growth during fermentation [ 31 ]. -glucans also contribute to a regulation of satiety levels [ 32 ] and act as thickening agents, increasing product viscosity [ 33 ] and avoiding the addition of other functional ingredients or stabilizers [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the practical, economic, and ethical limitations of in vivo intervention trials, in vitro colonic fermentation simulation with digestion models is considered to be a good approach for studying the metabolism and bioavailability of foods rich in polyphenols. Several in vitro digestion models combined with simulated intestinal fermentation models using human or mouse fecal inoculation have been used as valuable alternatives to in vivo studies [ 19 , 29 , 30 , 31 ]. However, since in vitro simulations cannot be exactly the same as in vivo conditions, verification through animal and/or human studies remains imperative.…”
Section: Discussionmentioning
confidence: 99%
“…It is because fermentation in pure bacterial culture does not consider the interactions between microbes. For example, although strain specific, the in vitro fermentation of oat β-1,3-1,4-glucan and its hydrolyzed fragments with pure probiotic culture Lactobacillus helveticus , Lactobacillus rhamnosus and Bifidobacterium longum showed that growth and total SCFAs production was highest with glucose, followed by hydrolyzed derivative and then the original oat β-glucan [23]. Important elements of research in microbial community ecology include the analysis of functional pathways for nutrient resource and energy flows, mechanistic understanding of interactions between microbial populations and their environment, and the emergent properties of the complex community [24].…”
Section: Discussionmentioning
confidence: 99%